Keystone effects of prairie dogs (Cynomys spp.) on grassland birds: Current knowledge and future directions - R. Andrew Dreelin; Andy J. Boyce; Holly P. Jones (Conservation Science and Practice)
Abstract Keystone species are critical to maintaining ecological relationships and ecosystem functioning around the world. Prairie dogs (Cynomys sp.) are a genus of colonial keystone species endemic to North American grasslands that modify bird community composition via ecological disturbance, but this topic has not been reviewed despite many studies on grassland bird associations with prairie dogs. We conducted a systematic literature review (n = 111 studies) where we assessed three hypotheses and found consistent support for each: (1) prairie dogs increase abundance of early‐successional grassland birds through grazing, (2) prairie dog towns modify bird community composition compared to nearby grassland because they increase heterogeneity within grasslands at large spatial scales, and (3) prairie dogs increase raptor abundance by serving as a prey base. Significant gaps in our understanding of the effects of prairie dogs on birds remain. Most research was conducted on black‐tailed prairie dogs during the bird breeding season and focused on how prairie dogs modify the occurrence and abundance of birds. Research is needed on the effects of other prairie dog species, effects on birds during the non‐breeding or migratory seasons, and effects on demography, particularly for songbirds. Continued work on this topic can increase our understanding of how keystone species affect bird communities and inform conservation of grassland birds globally. Due to rapid declines of grassland birds in North America, we suggest conserving prairie dog towns as vital sources of early successional grassland and habitat heterogeneity.